2002
DOI: 10.1063/1.1483117
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresponse force microscopy for polarity imaging of GaN

Abstract: The polarity distribution of GaN based lateral polarity heterostructures is investigated by piezoresponse force microscopy (PFM). Simultaneous imaging of surface morphology, as well as the phase and magnitude of the piezoelectric response, is performed by PFM on a GaN film with patterned polarities on a c-Al2O3 substrate. We demonstrate that the polarity distribution of GaN based lateral polarity heterostructures can be deduced from the phase image of the piezoresponse with nanometer scale spatial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 22 publications
2
59
1
2
Order By: Relevance
“…9,10 A slightly higher piezoresponse observed for the N-face regions was associated with a larger total polarization and the correspondingly larger bound surface charge. 9 This was consistent with Raman measurements of the relative peak shifts across the IDBR. 10 The measurements indicated that the N-face region is under less compressive stress, which implies a smaller piezoelectric polarization and a larger total polarization for the N face.…”
Section: Introductionsupporting
confidence: 77%
“…9,10 A slightly higher piezoresponse observed for the N-face regions was associated with a larger total polarization and the correspondingly larger bound surface charge. 9 This was consistent with Raman measurements of the relative peak shifts across the IDBR. 10 The measurements indicated that the N-face region is under less compressive stress, which implies a smaller piezoelectric polarization and a larger total polarization for the N face.…”
Section: Introductionsupporting
confidence: 77%
“…(11)(12)(13)(14) thus describe static deflection at frequencies well below the first resonance. Note that the relative magnitudes of these contributions are, as expected, sensitive to the length of the cantilever and for stiff cantilevers, From Eqs.…”
Section: Iii2 Cantilever Dynamics In Pfmmentioning
confidence: 99%
“…9,10,11 It was shown recently that vector PFM can be used to determine local molecular or crystallographic orientation in piezoelectric materials, provided that all three components of electromechanical response vector are determined quantitatively. 12 Broad applicability of PFM to materials such as ferroelectric perovskites, piezoelectric III-V nitrides, 13 and, recently, biological systems such as calcified and connective tissues, 14,15,16 has necessitated fundamental theoretical studies of image formation mechanism in PFM to provide the guidelines for quantitative data acquisition and interpretation. It was recognized that electrostatic tip-surface forces and buckling oscillations of the cantilever can provide significant and in some cases even dominating contributions to the PFM signal.…”
Section: Introductionmentioning
confidence: 99%
“…PFM has been employed to determine the polarity in llJ-nitride thin films and bulk crystals [47][48][49]. PFM of a GaN-based LPH is shown in Figure 14.…”
Section: Measurement Of Polarity Effects By Spmmentioning
confidence: 99%
“…They employed scanning capacitance microscopy (SCM) to investigate threading dislocations in GaN. Since then, SCM [13][14][15], electrostatic force microscopy (EFM) [16][17][18][19][20], Kelvin probe force microscopy (KPFM) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36],conductive-tip atomic force microscopy (C-AFM) [35][36][37][38][39][40][41][42][43][44][45][46], piezoresponse force microscopy (PFM) [47][48][49][50] and scanning gate microscopy (SGM) [51] have all been employed to characterize III-nitride films and surfaces.…”
Section: Introductionmentioning
confidence: 99%